The Numerical Calculation Of Hybrid Conjugate Gradient Method Under Armijo Line Search And Its Application - Norhaslinda Zullpakkal; Syazwani Mohd Zokri; Mohd Rivaie; Norrlaili Shapiee (Penerbit UTM Press, 2024)
Indexed by WOS/MyCite